Eco's Echoes: Fictional Theory and Detective Practice in The Name of the Rose - David H. Richter (Studies in 20th & 21st Century Literature, 1986)
Umberto Eco's The Name of the Rose is a serio-comic pastiche of the detective story set in the middle ages, which uses history as "a distant mirror" to comment, from a Western Marxist perspective, on contemporary political issues. Structurally, however, The Name of the Rose is a fictional enactment of many of the semiotician's recent critical and philosophical ideas. ( 1) Eco's discussion of "abductive" reasoning in C. S. Peirce and Aristotle appears in a detective not only more fallible than Sherlock Holmes but more aware of what his powers consist of and why they work and fail. (2) Eco's explanation of what he calls the "iterative scheme" in popular fiction—ways of handling time that allow for indefinite sequelae—appears negatively here, where time and time's passage are given their full durational weight. (3) Eco's discussion of closed and open texts, and of a third category "of which the chairman is probably Tristram Shandy," which evades both modes of reading and forces one into consciousness of the reading process itself, is enacted in The Name of the Rose, in a traditionally closed genre (the mystery) which is first opened but finally given an ending that deconstructs the mystery novel by forcing the reader into the third, Shandean, mode.
Keywords: Umberto Eco; Italian literature; fictional theory; The Name of the Rose; detective story; Wester Marxist; marxism; philosophy; reasoning; reason; C.S. Peirce; Aristotle; iterative scheme; consciousness; mystery novel; Shandean mode